Composite silicon nanostructure arrays fabricated on optical fibre by chemical etching of multicrystal silicon film. (24th March 2015) - Zuo, Zewen; Zhu, Kai; Ning, Lixin; Cui, Guanglei; Qu, Jun; Huang, Wanxia; Shi, Yi; Liu, Hong
Abstract: Integrating nanostructures onto optical fibers presents a promising strategy for developing new-fashioned devices and extending the scope of nanodevices' applications. Here we report the first fabrication of a composite silicon nanostructure on an optical fiber. Through direct chemical etching using an H2 O2 /HF solution, multicrystal silicon films with columnar microstructures are etched into a vertically aligned, inverted-cone-like nanorod array embedded in a nanocone array. A faster dissolution rate of the silicon at the void-rich boundary regions between the columns is found to be responsible for the separation of the columns, and thus the formation of the nanostructure array. The morphology of the nanorods primarily depends on the microstructure of the columns in the film. Through controlling the microstructure of the as-grown film and the etching parameters, the structural control of the nanostructure is promising. This fabrication method can be extended to a larger length scale, and it even allows roll-to-roll processing.